# Dorin Marghidanu's Cyclic Inequality with Constraint

### Statement

### Solution 1

The inequality is equivalent to

$\displaystyle 2a^2-2\sqrt{2}(b+c)a+3b^2+4c^2-2\sqrt{bc}\gt 0.$

But

$\begin{align} &2a^2-2\sqrt{2}(b+c)a+3b^2+4c^2-2\sqrt{bc}\\ &\qquad\qquad=(b+c-\sqrt{2}a)^2+(2b^2-2(1+\sqrt{2})bc+3c^2)\\ &\qquad\qquad\ge 2b^2-2(1+\sqrt{2})bc+3c^2. \end{align}$

Now, the discriminant of the quadratic form $2b^2-2(1+\sqrt{2})bc+3c^2\,$ equals $2\sqrt{2}-3\lt 0\,$ so that the form is never negative. In addition, it only vanishes for $b=c=0\,$ which is incompatible with the constraint $ab+bc+ca=1.\,$ Therefore, under the constraint, $2b^2-2(1+\sqrt{2})bc+3c^2\gt 0\,$ and the same holds for the whole expression:

$\displaystyle 2a^2+3b^2+4c^2=2a^2-2\sqrt{2}(b+c)a+3b^2+4c^2-2\sqrt{bc}\gt 0.$

### Solution 2

$\begin{align} &2a^2+3b^2+4c^2 = (a^2+2b^2)+(b^2+2c^2)+(a^2+2c^2)\\ &\qquad=(a-\sqrt{2}b)^2+(b-\sqrt{2}c)^2+(a-\sqrt{2}c)^2+2\sqrt{2}(ab+bc+ca)\\ &\qquad\ge 2\sqrt{2}\cdot 1=2\sqrt{2}. \end{align}$

### Solution 3

By the AM-GM inequality,

$a^2+2b^2\ge 2\sqrt{2}ab,\\ b^2+2c^2\ge 2\sqrt{2}bc.\\ a^2+2c^2\ge 2\sqrt{2}ca.$

Adding up, and taking into account the constraint, yields the required inequality.

### Solution 4

Observe that, for any $\lambda\in (0,3]\,$ and any $\mu\in (0,4],$

$a^2+\lambda b^2\ge 2\sqrt{\lambda}ab,\\ (3-\lambda)b^2+\mu c^2\ge 2\sqrt{(3-\lambda)\mu}bc.\\ a^2+(4-\mu)c^2\ge 2\sqrt{4-\mu}ca.$

By adding the three we have

$2a^2+3b^2+4c^2\ge 2(\sqrt{\lambda}ab+\sqrt{(3-\lambda)\mu}bc+\sqrt{4-\mu}ca).$

To make use of the constraint, we now require $\lambda=(3-\lambda)\mu=4-\mu\,$ which is satisfied with $\lambda=\mu=2.\,$ Thus the three inequalities above become

$a^2+2b^2\ge 2\sqrt{2}ab,\\ b^2+2c^2\ge 2\sqrt{2}bc.\\ a^2+2c^2\ge 2\sqrt{2}ca.$

The first with equality if $a=\pm\sqrt{2}b,\,$ the second becomes equality if $b=\pm\sqrt{2},\,$ and the third, if $a=\pm\sqrt{2}c.\,$ The three are only satified with $a=b=c=0,\,$ which is incompatible with the given constraint. As a consequence, we arrive at the strict inequality

$\displaystyle 2a^2+3b^2+4c^2 \ge 2\sqrt{2}(ab+bc+ca)=2\sqrt{2}.$

### Solution 5

Let $f=2a^2+3b^2+4c^2.\,$ Replacing $\displaystyle a=\frac{1-bc}{b+c},\,$ $f=3b^2+4c^2+\displaystyle\frac{2(1-bc)}{(b+c)^2}.\,$ The derivatives:

$\displaystyle \nabla=\left(\begin{array}{c}\,6b+\frac{4c(-1+bc)}{(b+c)^2}-\frac{4(-1+bc)^2}{(b+c)^3}\\ \frac{4(-1+2c(b+c)^3+b(c+b(-1+bc)))}{(b+c)^3}\end{array}\right).$

Setting $\nabla=0,\,$ we have a tighter bound (going through complex expressions of a real solution) of

$\displaystyle \min(f)=-3+3^{\frac{1}{3}}\left((7-4i\sqrt{2})^{\frac{1}{3}}+(7+4i\sqrt{2})^{\frac{1}{3}}\right)\approx 2.84667,$

which is tighter than $2\sqrt{2}\approx 2.82843.\,$ (The corresponding $b,c\,$ are real.)

wolframalpha gives that value as $\displaystyle 6\cdot \cos\left(\frac{2}{3}\arctan\left(\frac{1}{2\sqrt{2}}\right)\right)-3.$

Here's additional verification

### Solution 6

$\displaystyle\begin{align} &\bigg\{\sqrt{2}a-(b+c)\bigg\}^2+\left\{\sqrt{2}b-\left(1+\frac{1}{\sqrt{2}}\right)c\right\}^2\\ &\qquad&\qquad\qquad +\left\{\left(1-\frac{1}{\sqrt{2}}\right)c\right\}^2+2\sqrt{2}(ab+bc+ca)\\ &\qquad\qquad\ge 2\sqrt{2}(ab+bc+ca)=2\sqrt{2}. \end{align}$

Equality could be possible when simultaneously $\sqrt{2}a=b+c,\,$ $\displaystyle \sqrt{bb}=\left(1+\frac{1}{\sqrt{2}}\right)c\,$ $\displaystyle\left(1-\frac{1}{\sqrt{2}}\right)c=0,\,$ $ab+bc+ca=1,\,$ i.e., never as the four conditions are incompatible.

### Solution 7

This solution has been placed on a separate page.

### Acknowledgment

The problem has been kindly posted by Dorin Marghidanu at the CutTheKnotMath facebook page, along with Leo Giugiuc's solution (Solution 1). Originally, the problem appeared at the The School Olympiad facebook group where I found a solution (Solution 2) by Ravi Prakash and another (Solution 3) by Imad Zak; Solution 4 is by Dorin Marghidanu. Athina Kalampoka has independently arrived at Solution 2. The computer assisted Solution 5 is by Nassim Nicholas Taleb; Solution 6 is by Kunihiko Chikaya; Solution is by Le Khanh Sy.

- A Cyclic But Not Symmetric Inequality in Four Variables
- An Inequality with Constraint
- An Inequality with Constraints II
- An Inequality with Constraint III
- An Inequality with Constraint IV
- An Inequality with Constraint VII
- An Inequality with Constraint VIII
- An Inequality with Constraint IX
- An Inequality with Constraint X
- Problem 11804 from the AMM
- Sladjan Stankovik's Inequality With Constraint
- An Inequality with Constraint XII
- An Inequality with Constraint XIV
- An Inequality with Constraint XVII
- An Inequality with Constraint in Four Variables II
- An Inequality with Constraint in Four Variables III
- An Inequality with Constraint in Four Variables V
- An Inequality with Constraint in Four Variables VI
- A Cyclic Inequality in Three Variables with Constraint
- Dorin Marghidanu's Cyclic Inequality with Constraint
- Dan Sitaru's Cyclic Inequality In Three Variables with Constraints
- Dan Sitaru's Cyclic Inequality In Three Variables with Constraints II
- Dan Sitaru's Cyclic Inequality In Three Variables with Constraints III
- Inequality with Constraint from Dan Sitaru's Math Phenomenon
- Another Problem from the 2016 Danubius Contest
- Gireaux's Theorem
- An Inequality with a Parameter and a Constraint
- Unsolved Problem from Crux Solved
- An Inequality With Six Variables and Constraints
- Cubes Constrained
- Dorin Marghidanu's Inequality with Constraint
- Dan Sitaru's Integral Inequality with Powers of a Function
- Michael Rozenberg's Inequality in Three Variables with Constraints
- Dan Sitaru's Cyclic Inequality In Three Variables with Constraints IV
- An Inequality with Arbitrary Roots
- Leo Giugiuc's Inequality with Constraint
- Problem From the 2016 IMO Shortlist
- Dan Sitaru's Cyclic Inequality with a Constraint and Cube Roots
- Dan Sitaru's Cyclic Inequality with a Constraint and Cube Roots II
- A Simplified Version of Leo Giugiuc's Inequality from the AMM
- Kunihiko Chikaya's Inequality $\displaystyle \small{\left(\frac{(a^{10}-b^{10})(b^{10}-c^{10})(c^{10}-a^{10})}{(a^{9}+b^{9})(b^{9}+c^{9})(c^{9}+a^{9})}\ge\frac{125}{3}[(a-b)^3+(b-c)^3+(c-a)^3]\right)}$
- A Cyclic Inequality on [-1,1] $\left(xy+yz+zx\ge 1\right)$
- An Inequality with Two Triples of Variables $\left(\displaystyle\sum_{cycl}ux\ge\sqrt{\left(\sum_{cycl}xy\right)\left(2\sum_{cycl}uv-\sum_{cycl}u^2\right)}\right)$
- 6th European Mathematical Cup (2017), Junior Problem 4 $\left(x^3 - (y^2 + yz + z^2)x + y^2z + yz^2 \le 3\sqrt{3}\right)$
- Dorin Marghidanu's Example $\displaystyle\frac{\displaystyle\frac{1}{b_1}+\frac{2}{b_2}+\frac{3}{b_3}}{1+2+3}\ge\frac{1+2+3}{b_1+2b_2+3b_3},$

|Contact| |Front page| |Contents| |Algebra|

Copyright © 1996-2018 Alexander Bogomolny62827413 |